2015
DOI: 10.1161/atvbaha.114.305127
|View full text |Cite
|
Sign up to set email alerts
|

Platelet CD40L Modulates Thrombus Growth Via Phosphatidylinositol 3-Kinase β, and Not Via CD40 and IκB Kinase α

Abstract: Objective— To investigate the roles and signaling pathways of CD40L and CD40 in platelet–platelet interactions and thrombus formation under conditions relevant for atherothrombosis. Approach and Results— Platelets from mice prone to atherosclerosis lacking CD40L ( Cd40lg −/− Apoe −/− ) showed diminished α IIb β 3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 47 publications
(58 reference statements)
2
35
0
Order By: Relevance
“…26 Therefore, we hypothesize that TRAF3 expression may be higher in the vascular recurrence patients, which might increase the CD40 ligand signal transduction, thereby enhancing platelet-platelet interactions, secretion, and thrombus growth under artherogenic conditions. 27 In addition to the association with vascular recurrence in on-clopidogrel treatment patients, we also found that lower cg03548645 DNAm levels were correlated with higher platelet aggregation (ADP-induced platelet aggregation; P=0.0075). This association indicates that epigenetics might be involved in the vascular recurrence of stroke and in the pharmacodynamics of clopidogrel.…”
Section: Discussionsupporting
confidence: 53%
“…26 Therefore, we hypothesize that TRAF3 expression may be higher in the vascular recurrence patients, which might increase the CD40 ligand signal transduction, thereby enhancing platelet-platelet interactions, secretion, and thrombus growth under artherogenic conditions. 27 In addition to the association with vascular recurrence in on-clopidogrel treatment patients, we also found that lower cg03548645 DNAm levels were correlated with higher platelet aggregation (ADP-induced platelet aggregation; P=0.0075). This association indicates that epigenetics might be involved in the vascular recurrence of stroke and in the pharmacodynamics of clopidogrel.…”
Section: Discussionsupporting
confidence: 53%
“…Corroborating our previous studies, no differences in P-selectin or αIIbβ3 integrin activation were detected between Cd40 −/− Apoe −/− and Apoe −/− platelets in any of the experimental conditions ( Figure IA and IB in the online-only Data Supplement). 39 In addition, collagen-or ADP-induced platelet aggregation in whole blood was not affected by deficiency of CD40 ( Figure 1A and 1B). However, supernatants of thrombin-activated platelets displayed a significant decrease in chemokine (C-X-C motif) ligand 4, identifying platelet CD40 as a prominent mediator of inflammation rather than a regulator of thrombosis ( Figure 1C).…”
Section: Deficiency Of Platelet Cd40 Does Not Impair Platelet Activationmentioning
confidence: 88%
“…38 In addition, we recently showed that CD40L-deficient platelets prevent GP VI-dependent dense thrombus formation on collagen or atherosclerotic plaque material. 39 Conversely, addition of CD40L enhanced GP VI-induced platelet aggregation via integrin αIIbβ3 and phosphatidylinositol-4,5-bisphosphate 3-kinase, but independent of inhibitor of nuclear factor κ-B kinase subunit α/nuclear factor κ-light-chain-enhancer of activated B cells. 39 Interestingly, platelets also express substantial levels of the alleged counter-receptor for CD40L, ie, CD40, 40,41 but its role has only been summarily described and suggests a role in thrombus formation.…”
mentioning
confidence: 97%
See 2 more Smart Citations